2009
DOI: 10.1542/peds.2008-2233f
|View full text |Cite
|
Sign up to set email alerts
|

Complex Interactions of Pollutant and Allergen Exposures and Their Impact on People With Asthma

Abstract: Pediatric asthma has many causes and can manifest differently in different children and at different times. Understanding the many factors related to the development and exacerbation of asthma is complicated by the complexity of the many environmental exposures related to asthma development and morbidity. Furthermore, the same environmental exposures that may cause increased symptoms at 1 point in time may be protective when the exposure occurs earlier or at high enough levels. We know that environmental expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…Eggleston (2009) concluded that "the same environmental exposures that may cause increased symptoms at one point in time may be protective when the exposure occurs earlier or at high enough levels".…”
Section: Interactions With Aeroallergensmentioning
confidence: 99%
“…Eggleston (2009) concluded that "the same environmental exposures that may cause increased symptoms at one point in time may be protective when the exposure occurs earlier or at high enough levels".…”
Section: Interactions With Aeroallergensmentioning
confidence: 99%
“…The risks of engaging in outdoor activities or living near heavily polluted roadways are associated with the development of asthma in childhood and subsequently diminished lung function. In addition, as Eggleston 16 notes, children with asthma come into contact with bioactive pollutants and allergens simultaneously. He indicates that many of these small-molecule pollutants likely serve as adjuvants to magnify the immunoglobulin E-mediated inflammation that is characteristic of asthma in children.…”
Section: Systems Changes In Asthma Management and Access To Carementioning
confidence: 99%
“…For example, asthma morbidity can negatively influence the psychosocial environment of both the child with asthma and the family, and this can decrease the effectiveness of the child's asthma management, leading to increased asthma morbidity. 17 As Eggleston 16 points outs, the effects of allergen exposures can be accentuated by environmental pollution or viral infections. Additional complexity results from the fact that not all of these factors interact in the same way for all children.…”
Section: Systems Changes Through Implementation Of Proven Asthma Intementioning
confidence: 99%
“…To help advance understanding of the relationships between ambient air pollutant concentrations and asthma exacerbations in children, further characterization of the dose-response and pollutant lag effects are needed, as are investigations of pollutant species beyond the commonly measured urban air pollutants (3,7). Further investigation of pollutant mixtures and effect modification may also provide insights (8,9); for example, there have been reports of stronger pollution effects during the warm season (10-15) even though pediatric asthma rates peak during the cold season (16). To lessen concerns about uncontrolled confounding, aggressive control for variables, such as meteorology and seasonal asthma trends, is required.…”
mentioning
confidence: 99%
“…Our study takes advantage of daily measurements of components of particulate matter less than 2.5 mm in aerodynamic diameter (PM 2.5 ), a resource not typically available to investigators, which enables us to distinguish among the various compounds that comprise PM 2.5 . We investigated effect modification by season and potential confounding by ambient pollen concentrations and upper respiratory infections, because it is well known that these factors can trigger asthma exacerbations (9). The extent to which ambient pollen concentrations and circulating respiratory viruses confound associations between air pollutant concentrations and asthma exacerbations depends on the nature of the associations between short-term…”
mentioning
confidence: 99%